Assessing ecosystem-based farm management practices in the Kassena-Nankana area: a Study of government and community managed irrigation schemes. - Agula, C. (2017)
The contribution of irrigation farming to food security, nutrition, employment and poverty alleviation cannot be overemphasized in the savannah zone of Ghana of which Kassena-Nankana area is part. The main objective of the study was to assess the use of ecosystem-based farm management practices (EBFMPs) in government and community managed irrigation schemes within the Kassena-Nankana area and how these EBFMPs affect farmers’ livelihood. The study used data collected from 300 irrigating households (150 each for government managed irrigation scheme (GIS) and community managed irrigation schemes (CIS)). Farmers’ willingness to pay for EBFMPs sustainability was elicited by the contingent valuation method (CVM). The Poisson and negative binomial models, which were employed to determine the factors that influence farmers’ intensity of using EBFMPs indicated that age, distance of irrigated farm from home, farmers’ perception of soil fertility, farmers’ knowledge of EBFMPs, number of extension visits and the type of irrigation scheme were statistically significant. The t-test (mean comparison) also concluded that farmers under CIS significantly have higher mean willingness to pay (WTP) amount than those under the GIS. It was also revealed by a treatment effect model (regression adjustment) that a decision to use high number of EBFMPs causes an improvement on farmers’ average livelihood status score (ALSS), which is significant at 1%. The study concluded that there was low adoption of EBFMPs by farmers in the study area. However, those under CIS employed more EBFMPs than those under GIS. The study therefore recommends that policy implementers and development partners should revise their “yield emphasis” and intensify their extension activities to educate farmers on the use of EBFMPs. Again, the study recommends that more programs and projects should be tailored on sustainable production systems since those have greater positive impact on farmers’ livelihoods.